Do We Have to Consider International Capital Mobility in Trade Models? - Katrin Springer (Kiel Institute of World Economics (IfW), 2000)
The traditional trade theory predicts that trade in goods perfectly substitutes for direct movement of factors. This equivalence between goods trade and factor movements, however, depends crucially on assumptions about the production. This paper establishes necessary and sufficient conditions which describe the relationship between goods trade and capital mobility in a 2x2x2 trade model with internationally mobile capital. It identifies possible ways of incorporating capital mobility into a multi-regional, multi-sectoral Computable General Equilibrium framework. The consideration of capital mobility leads to other allocational and distributional outcomes of policy scenarios if there exists differences in production technologies across regions, trade impediments, or distortions in product or factor markets.
Keywords: 330; Capital Mobility; International Trade; Computable General Equilibrium Model; Aussenwirtschaftstheorie; Internationale Kapitalmobilität; Zwei-Länder-Modell; Mehr-Sektoren-Modell; Allgemeines Gleichgewicht; Internationaler Finanzmarkt; Direktinvestition; Theorie